PEMANFAATAN MEDIA DIGITAL WEB GOOGLE SITES DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKS CERITA INSPIRATIF - MURNIASIH MURNIASIH; LAILY NURLINA (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2023)
This study aims to describe the difficulties experienced by students in writing inspirational story texts. The research method in this study is descriptive qualitative with an emphasis on case study research. The data analysis technique used is descriptive analysis technique which is performed to assess the characteristics of a data using a procedure with an analysis model and the results of a written test conducted. The subjects of this research were students of class IX B at SMP Negeri 1 Rawalo. The difficulties experienced by students were caused by the lack of students practicing writing essays, difficulty determining topics to be raised, difficulties developing writing frameworks based on structural patterns, difficulties arranging events into plots, difficulties making conflicts from selected events, and when writing an essay students tend to experience difficulty in constructing effective sentences. In addition, because in the learning process which is still conventional, it does not utilize digital media. This proves that students' difficulties in writing inspirational story texts are caused by students' lack of mastery in terms of text structure and conventional learning. One of the right media in the process of making teaching materials is by utilizing Google Web digital media. Based on the results of the research that has been carried out in the research results table, it explains that Google Sites digital web media can be used as a medium or learning method in the classroom, especially in the 21st century and the technological industrial revolution, with the presence of Google Sites digital media, it is hoped that students will be more interested in participating in the learning process fun and interesting and on the side of students. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan kesulitan yang dialami siswa dalam menulis teks cerita inspiratif. Metode  penelitian  dalam  penelitian  ini  yaitu  deskriptif  kualitatif dengan menitikberatkan pada penelitian studi kasus.   Teknis  analisis  data  yang  digunakan yaitu teknik analisis deskriptif yang dilakukan untuk menilai karakteristik dari sebuah data menggunakan prosedur dengan model analisis dan hasil tes tertulis yang dilakukan. Subjek penelitian ini adalah siswa kelas IX B di SMP Negeri 1 Rawalo. Kesulitan yang dialami siswa disebabkan oleh kurangnya siswa berlatih menulis karangan, kesulitan menentukan topik yang akan diangkat, kesulitan mengembangkan kerangka tulisan berdasarkan pola struktur, kesulitan menyusun peristiwa menjadi alur, kesulitan membuat konflik dan dari peristiwa yang dipilih, dan ketika menulis suatu karangan siswa cenderung mengalami kesulitan dalam menyusun kalimat yang efektif. Selain itu juga karena dalam proses pembelajaran yang masih konvensional tidak memanfaatkan media digital. Hal ini membuktikan bahwa kesulitan siswa dalam menulis teks cerita inspiratif disebabkan oleh kurangnya penguasaan siswa dalam hal struktur teks dan pembelajaran yang masih konvensional. Salah satu  media yang tepat dalam proses pembuatan bahan ajar yaitu dengan memanfaatkan media digital Web Google. Berdasarkan hasil penelitian yang telah dilaksanakan pada tabel hasil penelitian, menjelaskan bahwa media digital web Google Sites dapat digunakan sebagai media atau metode pembelajaran di dalam kelas terutama di abad 21 dan revolusi industri teknologi, dengan hadirnya media digital Google  Sites diharapkan siswa lebih tertarik mengikuti proses pembelajaran yang menyenangkan dan menarik serta berpihak pada siswa.